2016
DOI: 10.1136/bcr-2015-214104
|View full text |Cite
|
Sign up to set email alerts
|

Glossopharyngeal neuralgia associated with cardiac syncope

Abstract: Glossopharyngeal neuralgia is a rare pain syndrome presenting with paroxysms of pain in the region of the glossopharyngeal nerve. Even more uncommon is the association between glossopharyngeal neuralgia and cardiac syncope. In these patients, the cardiovascular consequences may include bradycardia, hypotension and cardiac arrest. We describe the case of a 40-year-old patient who presented with this rare association of glossopharyngeal neuralgia and syncope. Multiple pauses including one lasting 14 s were noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Only three patients in this group had symptoms of episodic arrhythmias such as bradycardia but had no serious events such as syncope. In fact, severe syncope symptoms have been rarely reported internationally; Burfield et al ( 20 ) and Aguiar et al ( 21 ) have reported relevant cases.…”
Section: Discussionmentioning
confidence: 99%
“…Only three patients in this group had symptoms of episodic arrhythmias such as bradycardia but had no serious events such as syncope. In fact, severe syncope symptoms have been rarely reported internationally; Burfield et al ( 20 ) and Aguiar et al ( 21 ) have reported relevant cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no declared glossopharyngeal-vagal reflex, the occurrence of vagal syncope during glossopharyngeal neuralgia indicates that there should be a relationship between the glossopharyngeal and vagus nerves. [10] Most proposed mechanisms are based on the close anatomical relationship between the glossopharyngeal and vagus nerves in the medulla oblongata and the possibility of vagoglossopharyngeal reflex arc formation. [11] Another view suggests that some visceral sensory fibers of the glossopharyngeal nerve might connect with fibers of the carotid sinus nerve (nerve of Hering), stimulating the latter; therefore, activation of the baroreceptors of the carotid sinus, resulting in bradycardia, asystole, premature atrial contractions, or hypotension that can lead to syncope.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that vascular compression of the IXth nerve causes the neuralgia, and a simultaneous compression of the Xth nerve triggers a direct parasympathetic outflow to the heart [ 13 ]. The other hypothesis is that the compression of the IXth nerve causes the neuralgia but also triggers impulses from what would be Hering's nerve to travel up to the brainstem (to the nucleus tractus solitarius) which then senses a false hypertension and triggers a reflexive bradycardia down the vagus nerve [ 14 , 15 ]. Our results support the second hypothesis for two reasons.…”
Section: Discussionmentioning
confidence: 99%